GC-MS Profiling and Pathogenic Effect of Khaya Anthotheca Methanolic Leaves Extract on Some Selected Fungi - Umaru, Isaac John; Shadrach, Philip; Adi, Godwin Baaku; Ugoeze, Egeonu Stephen; Nanmar, Chakfa; Akafa, Andes Tensaba; Umaru, Kerenhappuch Isaac; David, Bando Christopher (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This research evaluated GC-MS profile, and pathogenic effect of methanolic leaves extracts of Khaya anthotheca on Some Selected fungi. Khaya anthotheca a member of Meliaceae family is traditionally used for treating several ailments. The leaves were harvested in Sukundi road Wukari and air dried for four weeks, the leaves were pulverized into powder using manual blender and stored in an air tight container. Extraction was done with absolute methanol; the extract was filtered using mesh and the filtrate was concentrated at 68oC. Only two grams of the filtrate were used for the GC-MS study. One-way analysis of variance (ANOVA) was used for statistical analysis. The GC-MS result revealed 50 constituents. Result of Methanolic extracts of leaves of Khaya anthotheca only showed significant activity against Aspergillus niger at dose100 µg/mL, Candida tropicalis and Fusarium oxysporium at dose 500 µg/mL. This study supports the use of Khaya anthotheca by indigenous herbalists by providing scientific proof of the plant's ability to treat pothegenic diseases. To establish the effectiveness of this plant in the management of fungal effections, more clinical trials at the clinical levels are needed.